Sinetectula gen. nov., a new genus of Pisaniidae (Gastropoda: Buccinoidea) from the tropical Indian and Pacific Oceans - Fraussen, Koen; Vermeij, Geerat J. (European Journal of Taxonomy, 2021)
The genus Sinetectula gen. nov. is proposed to accommodate Triton egregius Reeve, 1844, Buccinum cinis Reeve, 1846, Buccinum nigricostatum Reeve, 1846, Buccinum (Pollia) farinosum Gould, 1850, Pisania naevosa Martens, 1880, Pollia shepstonensis Tomlin, 1926 and one still undescribed species. These species are discussed and compared, and remarks on their biogeography are provided. The occasional appearance of a labral denticle is recorded and the morphological variability of the group is discussed. The radula of S. egregius gen. et comb. nov. is described.